Extracellular vesicle-mediated pre-metastatic niche formation via altering host microenvironments - Li, Ying; Zheng, Yan; Tan, Xiaojie; Du, Yongxing; Wei, Yingxin; Liu, Shanglong (Frontiers in Immunology, 2024)
The disordered growth, invasion and metastasis of cancer are mainly attributed to bidirectional cell-cell interactions. Extracellular vesicles (EVs) secreted by cancer cells are involved in orchestrating the formation of pre-metastatic niches (PMNs). Tumor-derived EVs mediate bidirectional communication between tumor and stromal cells in local and distant microenvironments. EVs carrying mRNAs, small RNAs, microRNAs, DNA fragments, proteins and metabolites determine metastatic organotropism, enhance angiogenesis, modulate stroma cell phenotypes, restructure the extracellular matrix, induce immunosuppression and modify the metabolic environment of organs. Evidence indicates that EVs educate stromal cells in secondary sites to establish metastasis-supportive microenvironments for seeding tumor cells. In this review, we provide a comprehensive overview of PMN formation and the underlying mechanisms mediated by EVs. Potential approaches to inhibit cancer metastasis by inhibiting the formation of PMNs are also presented.